Zasada incompatibilitas w samorządowym prawie ustrojowym (relacje samorządowiec-parlamentarzysta) i projekt przekształcenia Senatu w Izbę Samorządową - Łukaszewski, Marcin (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The problem of Senate as a self-government chamber and self-government person – parliament deputy relations were shown in the political history of the Polish Third Republic many times. In 2001, when self-government laws were introduced into the political system of self-government, there was an institution of incompatibilitas (incompatibility of self-governmental and parliamentarian seats). It influenced the subsequent public debate about the role of Senate and the emerging plans to transform it into a self-government chamber.